The alternative Medicago truncatula defense proteome of ROS—defective transgenic roots during early microbial infection - Kiirika, Leonard M.; Schmitz, Udo; Colditz, Frank (Frontiers in Plant Science, 2014)
ROP-type GTPases of plants function as molecular switches within elementary signal transduction pathways such as the regulation of ROS synthesis via activation of NADPH oxidases (RBOH-respiratory burst oxidase homologue in plants). Previously, we reported that silencing of the Medicago truncatula GTPase MtROP9 led to reduced ROS production and suppressed induction of ROS-related enzymes in transgenic roots (MtROP9i) infected with pathogenic (Aphanomyces euteiches) and symbiotic microorganisms (Glomus intraradices, Sinorhizobium meliloti). While fungal infections were enhanced, S. meliloti infection was drastically impaired. In this study, we investigate the temporal proteome response of M. truncatula MtROP9i transgenic roots during the same microbial interactions under conditions of deprived potential to synthesize ROS. In comparison with control roots (Mtvector), we present a comprehensive proteomic analysis using sensitive MS protein identification. For four early infection time-points (1, 3, 5, 24 hpi), 733 spots were found to be different in abundance: 213 spots comprising 984 proteins (607 unique) were identified after S. meliloti infection, 230 spots comprising 796 proteins (580 unique) after G. intraradices infection, and 290 spots comprising 1240 proteins (828 unique) after A. euteiches infection. Data evaluation by GelMap in combination with a heatmap tool allowed recognition of key proteome changes during microbial interactions under conditions of hampered ROS synthesis. Overall, the number of induced proteins in MtROP9i was low as compared with controls, indicating a dual function of ROS in defense signaling as well as alternative response patterns activated during microbial infection. Qualitative analysis of induced proteins showed that enzymes linked to ROS production and scavenging were highly induced in control roots, while in MtROP9i the majority of proteins were involved in alternative defense pathways such as cell wall and protein degradation.